2022
DOI: 10.3390/land11010085
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Pattern of the Vitality of Chinese Characteristic Towns: A Perspective from Nighttime Lights

Abstract: Nighttime light images are valuable indicators of regional economic development, and nighttime light data are now widely used in town monitoring and evaluation studies. Using the nighttime light data acquired through Luojia1-01 and the geographic information system spatial analysis method, this study analyzed the spatial vitality pattern of 402 characteristic towns in six geographic divisions of China. The average DN (Digital Number) value of Guzhen, having the highest vitality level, was 0.05665221, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…DMSP/OLS nighttime light images were divided Land 2024, 13, 840 4 of 26 into five different types of nighttime light areas in another study to explore the relationship between dynamic spatial expansion patterns and spatiotemporal characteristics [38]. Research utilizing nighttime light data to analyze urban vitality found that cities with high vitality usually boast convenient transportation and rich historical or cultural heritage [39]. However, most studies have relied on a single data source to identify the patterns of association between urban vitality and other urban characteristics.…”
Section: Explorations Of Urban Vitality Assisted By Multisource Datamentioning
confidence: 99%
“…DMSP/OLS nighttime light images were divided Land 2024, 13, 840 4 of 26 into five different types of nighttime light areas in another study to explore the relationship between dynamic spatial expansion patterns and spatiotemporal characteristics [38]. Research utilizing nighttime light data to analyze urban vitality found that cities with high vitality usually boast convenient transportation and rich historical or cultural heritage [39]. However, most studies have relied on a single data source to identify the patterns of association between urban vitality and other urban characteristics.…”
Section: Explorations Of Urban Vitality Assisted By Multisource Datamentioning
confidence: 99%
“…(3) City Economic Vibrancy Index Compared with artificial statistics, nighttime light data can directly capture the spatial distribution of artificial radiation in human settlements with less error [33]. It can be used to visualize the real-time state of economic activity and intensity of human activity [34], and is commonly used to assess urban economic activity [35]. This study uses nighttime light data to quantify urban economic vibrancy by preprocessing the month-by-month lighting data using operations to remove lighting outliers and derive the average pixel value within each grid (P h,t ).…”
Section: Urban Vibrancy Indicators (1) City Social Vibrancy Indexmentioning
confidence: 99%
“…Although China's economy has begun to turn to connotative development, the construction of characteristic towns in different regions is still not ideal, and there exists a series of problems, including a lack of cultural support, insufficient benefit output, separation of life and production, and serious ecological destruction [5,6]. Some characteristic towns focus on their ecological maintenance and geographical development and pay too much attention to the external image, ignoring the development and integration of characteristic industries, which are not conducive to the sustainable development of the towns [7].…”
Section: Introductionmentioning
confidence: 99%